Analysis of the Influence of Content Marketing, Influencer Marketing and Online Customer Reviews on Purchase Decisions that Impact Customer Loyalty of Skintific Sunscreen Products in Dki Jakarta - Marlien Bokko; Andri Prasetiyo; Nana Nawasiah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The development of social media has changed people's consumption patterns and encouraged cosmetics companies to optimize their digital marketing strategies. Facing a competitive market, Skintific is required to maximize the role of content marketing, influencers, and online customer reviews to strengthen purchase decisions and maintain customer loyalty. The purpose of this study is to analyze the effect of content marketing, influencer marketing, and online customer reviews on purchase decisions and their impact on the loyalty of Skintific sunscreen customers in DKI Jakarta. The type of research is causal associative. Sampling was conducted using non probability sampling with purposive sampling techniques, and data collection was carried out using an online questionnaire. The sample size was 250 people. Data analysis was performed using PLS-SEM method. The results of the study indicate that content marketing, influencer marketing, and online customer reviews partially have a positive and significant effect on purchase decisions and customer loyalty. Purchase decisions are also proven to have a positive and significant effect on customer loyalty, and indirectly, content marketing, influencer marketing, and online customer reviews affect loyalty through purchase decisions for Skintific sunscreen in DKI Jakarta.